1993
DOI: 10.1136/bjo.77.7.417
|View full text |Cite
|
Sign up to set email alerts
|

A population based, prospective study of the development of ROP in prematurely born children in the Stockholm area of Sweden.

Abstract: A prospective population based study including 260 children with a birth weight of 1500 g or less was performed in the Stockholm county. The total incidence of retinopathy of prematurity (ROP) was 40*4%, while severe ROP -that is, stage 3 or more, was seen in 20.0%. Cryotherapy was performed in 10.8%. Logistic regression analysis revealed independent association of both gestational age and birth weight with ROP. The association of gestational age and ROP was significantly stronger, indicating that the degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
74
2
5

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 30 publications
5
74
2
5
Order By: Relevance
“…Some have found that there is a narrower range of CA 15 and others a narrower range of PMA 3,16 for the onset of the maximum stage of ROP. In our study, PMA gave a narrower range than CA (6 weeks cf 11 weeks).…”
Section: Age At Onset Of Maximum Ropmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have found that there is a narrower range of CA 15 and others a narrower range of PMA 3,16 for the onset of the maximum stage of ROP. In our study, PMA gave a narrower range than CA (6 weeks cf 11 weeks).…”
Section: Age At Onset Of Maximum Ropmentioning
confidence: 99%
“…As previous studies have shown a geographical variation in the incidence of threshold ROP in babies born at similar gestational ages, [2][3][4] it is important to continue to analyse screening data from different regions in order to inform the debate. It is likely that screening criteria will have to be specifically defined for particular populations.…”
Section: Introductionmentioning
confidence: 99%
“…The present study of neonatal risk factors for ROP is based on a population-based, prospective study of the epidemiology of ROP in a well defined geographic area (Holmströ m et al 1993). Two hundred and sixty infants with a birth weight of 1500 grams or less and with a survival of at least 8 weeks, were included in that study.…”
Section: Methodsmentioning
confidence: 99%
“…A prospective, population-based study of the epidemiology and natural history of retinopathy of prematurity (ROP) was performed in our area during 1988to 1990(Holmströ m et al 1993. Risk factors for ROP were also studied and a detailed analysis of maternal data from antenatal centres and labour rooms was recently published (Holmströ m et al 1996).…”
mentioning
confidence: 99%
“…Numerous studies have reported an increased risk of ROP in prematurely born infants, 1,2,3 but only a few have been long-term and strictly populationbased. 4,5 The 1995 Royal College of Ophthalmologists (RCO) guidelines for screening for ROP includes babies under 1500 g and gestational age Ͻ32 weeks and provides an effective and efficient means of detecting treatable ROP. These criteria present a considerable workload to the ophthalmologist and various authors have suggested it may be possible to lower the criteria and reduce the screened population of babies.…”
Section: Introductionmentioning
confidence: 99%